Private Sector Engagement in Adaptation to Climate Change: Approaches to Managing Climate Risks - Agrawala, Shardul (OECD Environment Working Papers, 2011)
There is growing international interest in the planning, financing and implementation of adaptation to climate change. However, the discussion to date has primarily focused on the public sector's role, with the private sector viewed primarily as a source of funding or financing. Relatively little attention has been paid to how the private sector is responding to the risks and opportunities from climate change. In this context, this analysis aims to contribute to a deeper understanding of private sector's role. This paper examines the private sector's progress in adapting to climate change by considering information from sixteen case studies, drawn from a range of industries across the private sector. This is complemented by a high-level analysis of broader private sector adaptation based on responses to the 2009 Carbon Disclosure Project questionnaire. The case studies provide insight into companies' awareness of potential climate risks and vulnerabilities, their progress in assessing specific impacts on their businesses and possible ways to respond to them, and their implementation of adaptation measures and strategies to manage these risks. The analysis also examines how companies are taking advantage of new business opportunities arising from climate change. The paper explores companies' motivations for implementing adaptation measures, and establishes common factors which can affect companies' capacities to adapt, their incentives for action, and their perspectives on the need to adapt. The analysis considers how these factors can both encourage and impede adaptation, and assesses potential public sector roles for eliminating barriers to action, encouraging engagement and incentivising private sector investment in adaptation